Pottery production, landscape and economy of Roman Dalmatia : interdisciplinary approaches - Lipovac Vrkljan, Goranka; Konestra, Ana (Archaeopress Roman archaeology, 2018)
This volume offers results of work undertaken as part of the RED project - Roman Economy in Dalmatia: production, distribution and demand in the light of pottery workshops. It presents research carried out on the Roman sites of pottery workshops active within the coastal area of the province of Dalmatia as well as on material recovered during the excavations. The presentation revolves around three thematic units: workshops and their products together with their role in the local provincial economy, location of workshops within the landscape, and archaeometric research which connects the two. These approaches contribute to the study of ceramic production in the area whereas new methodological approaches to the subject allow for the placement of pottery workshops in the broader context of Roman economy and landscape and natural resources of the eastern Adriatic.